The quality of peanut chocolate bar processed in Barangay Bubog, Talisay, Negros Occidental - Tan, Christine Cristoria (2004.)
The quality of peanut chocolate bar, produced by a small-scale food processor in Barangay Bubog, Talisay, Negros Occidental, was evaluated and established.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Peanut chocolate bar; Barangay Bubog, Talisay, Negros Occidental